Thực trạng quản lí hoạt động giáo dục đạo đức cho học sinh các trường trung học phổ thông huyện Ninh Phước, tỉnh Ninh Thuận - Bùi , Đức Tú; Đàng , Thị Hòa Hiệp (Tạp chí Giáo dục, 2024)
In recent time, the education sector has had many achievements but there are still many limitations, including the problem of the quality of moral education for students. The phenomenon of moral degradation, blurred ideals, and pursuit of a pragmatic lifestyle among some young people and students still exists, affecting the quality of moral education in society and schools. Moral education for students in high schools in Ninh Phuoc district, Ninh Thuan province has received attention, but there still exist some limitations and inadequacies due to the influence of a number of objective and subjective factors. The article surveys the current situation of moral education management for students in high schools in Ninh Phuoc district, Ninh Thuan province. The survey results will be the basis for proposing measures to manage ethical education activities for high school students in the area, contributing to improving the quality of ethical education for students in schools.